MIGRASI ETNIS TIONGHOA DI KABUPATEN YAPEN WAROPEN - Tolla, Marlin (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2010)
Migration by Tionghoa ethnic from the Chinese mainland especially southern part to the districts Yapen Waropen was in order to trade at that time,yapen is very famous with the wonderful products such as bird of paradise feathers, crocodile leather, and other excellent products that famous at that time. In the next stage, tionghoa ethnic marrying woman of yapen. This is done to facilitate them in obtaining merchandise from the Yapen people. Marriage between ethnic of tionghoa and yapen woman, produce offspring called Peranakan Chinese Serui (Prancis), Serui is the first name of Yapen.